2006
DOI: 10.1080/10826080601006508
|View full text |Cite
|
Sign up to set email alerts
|

Non Drug Use- and Drug Use-Specific Spirituality as One-Year Predictors of Drug Use Among High-Risk Youth

Abstract: The present article explored two different dimensions of spirituality that might tap negative and positive relations with adolescent drug use over a 1-year period. Non-drug-use-specific spirituality measured how spiritual the person believes he or she is, participation in spiritual groups, and engagement in spiritual practices such as prayer, whereas drug-use-specific spirituality measured using drugs as a spiritual practice. Self-report questionnaire data were collected during 1997-1999 from a sample of 501 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…This result is in consonance with findings from other studies [18,19]. These gateway substances have very high prevalence rates and eventually usher the user to experiment and abuse other more dangerous ones such as cocaine and heroine [20].…”
Section: Discussionsupporting
confidence: 92%
“…This result is in consonance with findings from other studies [18,19]. These gateway substances have very high prevalence rates and eventually usher the user to experiment and abuse other more dangerous ones such as cocaine and heroine [20].…”
Section: Discussionsupporting
confidence: 92%
“…Discussion T his pilot study provided evidence that college students such as the study participants were using hallucinogens for spiritual purposes. Two recent studies using surveys with predominantly Hispanic participants support the current study findings and suggest that hallucinogen use and not use of alcohol, marijuana, and stimulants may be associated with spiritual and religious purposes (Resor & Cooper, 2010;Sussman et al, 2006). Half of the current study participants were middleclass Caucasians, a demographic profile similar to the findings reported by Hunt (1997) as the population that was most likely to use hallucinogens.…”
Section: Hallucinogen Use and Openness To A Higher Powersupporting
confidence: 76%
“…In fact, Arria et al (2008) found that exposure to hallucinogens during the first two years of college increased the possibility of lifelong hallucinogen use. Sussman, Skara, Rodriguez, and Pokhrel (2006) explored the relationship between two different dimensions of spirituality in an ethnically diverse population of adolescents reporting drug use (cigarettes, alcohol, marijuana, hallucinogens, and stimulants) over a one-year period. Interestingly, the authors found that drug-use-specific spirituality was positively predictive of cigarette smoking and hallucinogen use, providing Keywords: hallucinogens, spirituality, college students, non-indigenous, recreational use…”
mentioning
confidence: 99%
“…This NUSI is a 7-item questionnaire that aims to measure an individual's perceived level of spirituality, participation in spiritual groups, and engagement in spiritual practices (Sussman, Skara, De Calice, Hoffman, & Dent, 2005). The NUSI has satisfactory internal reliability with an alpha coefficient of 0.80 (Sussman, Skara, Rodriguez & Pokhrel, 2006). In the present study the Cronbach alpha was 0.86.…”
Section: Religious Background and Behaviours (Rbb;mentioning
confidence: 60%